Pengembangan Asesmen Portofolio Elektronik Untuk Meningkatkan Habits of Mind Siswa Pada Materi Asam Basa - Agnes Suci Evriliani; Nahadi; Triannisa Rahmawati (Postgraduate, University of Mataram, 2025)
This study aimed to develop a valid and reliable electronic portfolio assessment instrument to support learning and potentially improve students’ habits of mind on acid-base material. Using a Research and Development (R&D) approach with the 4D model (Define, Design, Develop, and Disseminate), the instrument was tested on 30 eleventh-grade students in a public high school in Cimahi City. The habits of mind focused on three indicators: self-regulation, critical thinking, and creative thinking. The instrument included various tasks relevant to the acid-base topic. Validation results showed strong content validity (CVR = 1.00) and reliability (Cronbach’s Alpha values ranging from 0.70 to 1.00). A limited trial suggested potential improvements in students’ habits of mind, with observed levels of self-regulation categorized as medium to high, and critical and creative thinking ranging from low to high. However, these findings are preliminary, and further research using a more robust experimental design is needed to confirm the instrument’s effectiveness